A policy analysis regarding education, career, and governance of the nurses in Bangladesh: A qualitative exploration - Joarder, Taufique; Parvage, Md. Aslam; Rawal, Lal B.; Ahmed, Syed Masud (Sage Journals, 2022)
This article was published in BMJ Open by BMJ Journals [Copyright © 2021, © SAGE Publications] and the definite version is available at: https://doi.org/10.1177/1527154420988003 The Journal's website is at: https://journals.sagepub.com/doi/10.1177/1527154420988003